Wronged and dangerous: viral masculinity and the populist pandemic - Ashcraft, Karen Lee (Bristol University Press, 2022)
"COVID-19 delivers a stark warning: the global surge of populism endangers public health. 'Wronged and Dangerous' introduces 'viral masculinity' as a novel way to meet that threat by tackling the deep connection of our social and physical worlds. It calls us to ask not what populism says, but how it spreads."--